Evaluation of acute intradialytic complications, management & outcome in end-stage renal disease patients (Community Based Medical Journal, 2013)
Little is known about the challenges of routine renal replacement therapy in Bangladesh. We investigated the fatal and nonfatal acute hemodialysis complications in patients with end stage renal disease (ESRD) in dialysis centers in Mymensingh. 500 consecutive hemodialysis sessions incurred over a 4-month period by 50 patients with ESRD, receiving two weekly hemodialysis sessions of 4 hours each were considered. Personal and clinical profiles before, during, and within 24 hours after hemodialysis sessions were used to diagnose complications. The mean age of the patients was 45.5 ± 16.8 years and the lowest and highest ages were 17 and 82 years respectively. Male was predominant of the patients and male to female ratio was 2:1. Hypotension, muscular cramps, pruritus, nausea and vomiting were the common complications in end-stage renal disease patients. Twenty eight percent of patients presented with hypertensive crisis, 34% fever, 18% bleeding, 44% headache, 32% vomiting, 16% lumber pain, 16% palpitations, 22% disequilibrium syndrome, 36% dyspnea, 28% chest pain, 20% syncope, 32% abdominal problem, 44% neurological problem, 46% electrolyte imbalance, 34% articular & musculoskeletal problems, 48% cramps, 38% convulsions and 20% loss of consciousness. The vascular access was the main bleeding site of the patients (44.5%), followed by 33.3% through nose and 22.2% digestive tract bleeding. Most of patients experienced muscular cramps, hypertensive crisis, pruritus, vomiting, palpitations, disequilibrium syndrome, dyspnea, chest pain, neurologic problem, electrolyte disorders, nausea, vomiting, convulsions and loss of consciousness in shorter duration of dialysis than those in longer duration of dialysis sessions. Bleeding, disequilibrium syndrome and cardiovascular disease were leading cause of death in end-stage renal disease patients. Those complications occurred mostly during understaffed periods. Urgent strategies are needed to quickly solve the human capital crisis in the health care sector. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16696 Community Based Medical Journal 2013 July: Vol.02 No 02: 35-40